Population dynamics, sex ratio and size at sex change in a protandric simultaneous hermaphrodite, the spiny shrimp Exhippolysmata oplophoroides - Baeza, J. A.; Braga, A. A.; Lopez-Greco, L. S.; Perez, E.; Negreiros-Fransozo, M. L. [UNESP]; Fransozo, Adilson [UNESP] (Springer, 2010)
One of the main goals of sex allocation theory is understanding sex ratio evolution. However, theoretical studies predicting sex ratios in species with unusual sexual systems, such as protandric simultaneous (PS) hermaphroditism, are rare. In PS hermaphrodites, juveniles first develop into functional males that mature into simultaneous hermaphrodites later in life. Here, we report on the sex ratio (males/males + hermaphrodites) in the PS hermaphroditic shrimp Exhippolysmata oplophoroides. A 2-year study demonstrated that hermaphrodites dominated the population in two different bays. This skewed sex ratio may be explained by limited encounter rates among conspecifics. In agreement with this idea, the density of shrimps was extremely low (a parts per thousand currency sign1 shrimp km(-2)) at the two study sites. Size at sex phase change and sex ratios remained relatively stable through time at the two bays. The stability of these parameters might be explained by the rather steady population structure of this species during the study period. A review of sex ratios in PS hermaphroditic shrimps (Lysmata and Exhippolysmata) revealed considerable variation; some species have male- and others hermaphrodite-skewed sex ratios. The conditions explaining inter- and intra-specific sex ratio variation in protandric simultaneous hermaphroditic species remain to be addressed.